If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 1) = 8(x + -1) + -9 Reorder the terms: 3(1 + x) = 8(x + -1) + -9 (1 * 3 + x * 3) = 8(x + -1) + -9 (3 + 3x) = 8(x + -1) + -9 Reorder the terms: 3 + 3x = 8(-1 + x) + -9 3 + 3x = (-1 * 8 + x * 8) + -9 3 + 3x = (-8 + 8x) + -9 Reorder the terms: 3 + 3x = -8 + -9 + 8x Combine like terms: -8 + -9 = -17 3 + 3x = -17 + 8x Solving 3 + 3x = -17 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 3 + 3x + -8x = -17 + 8x + -8x Combine like terms: 3x + -8x = -5x 3 + -5x = -17 + 8x + -8x Combine like terms: 8x + -8x = 0 3 + -5x = -17 + 0 3 + -5x = -17 Add '-3' to each side of the equation. 3 + -3 + -5x = -17 + -3 Combine like terms: 3 + -3 = 0 0 + -5x = -17 + -3 -5x = -17 + -3 Combine like terms: -17 + -3 = -20 -5x = -20 Divide each side by '-5'. x = 4 Simplifying x = 4
| -17+2(2p-7)=5p | | 45x=20x^3 | | -4+5a=-4(7a+1) | | w+w+6+w+6+w=92 | | 2m^3-50m=0 | | 97-16x=-63 | | -4(6+7r)=-r+30 | | -6(4b+7)=-4(6b-7) | | 4(1x-6)+6=6x-8 | | 6x-1=9x-10 | | 7x+4=3x-52 | | 1r-10=10r+8 | | 4+6(k-8)=8k-38 | | 8-(-16)= | | x^3+5x^2+x^2-5x-12x-60=0 | | 5x(6-3)= | | 4w+5w=51 | | 10(8m+9)=10(6m-3) | | 8x+-8y=5 | | X-366=415 | | -5x+9=2x-4 | | x+3x+54+2x=180 | | 8p-8=8(-6p-8) | | 2x-6x+4=-12 | | 6x^2-8x-11=0 | | 4m^2-36m= | | x(3x+54)(2x)=180 | | 31=9t-13t+7 | | 19-13p=17p-8 | | (-3n+5)(-5.7)= | | 1.5+.3(h-6)=.8h+2 | | -[6x-(3x+5)]=-4-[4(2x-4)-3x] |